2020
DOI: 10.3389/fimmu.2020.01730
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis Suppurativa and 1-Carbon Metabolism: Role of Gut Microbiome, Matrix Metalloproteinases, and Hyperhomocysteinemia

Abstract: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin condition characterized by painful nodules which suppurate and later develop into scar tissues followed by the development of hypodermal tracts. Although the mechanisms behind HS are not fully understood, it is known that dietary factors play important roles in flare frequency and severity. We hypothesize that the high fat diet (HFD) causes dysbiosis, systemic inflammation, and hyperhomocysteinemia (HHcy) in susceptible individuals, which subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…They have shown that 72 h of post-injury was associated with a decrease in Bacteroidales, Fusobacteriales, and Verrucomicrobiales but an increase in Clostridiales and Enterococcus populations [149]. These findings provide the complex relation between and multiple disease outcomes, revealing the notion that bacterial populations indeed influence the post-injury mediated neuro-pathophysiology and functional impairment via dysbiosis-dependent mechanisms [150][151][152][153][154][155][156].…”
Section: Gmb-axis In Cns Injuriesmentioning
confidence: 94%
See 2 more Smart Citations
“…They have shown that 72 h of post-injury was associated with a decrease in Bacteroidales, Fusobacteriales, and Verrucomicrobiales but an increase in Clostridiales and Enterococcus populations [149]. These findings provide the complex relation between and multiple disease outcomes, revealing the notion that bacterial populations indeed influence the post-injury mediated neuro-pathophysiology and functional impairment via dysbiosis-dependent mechanisms [150][151][152][153][154][155][156].…”
Section: Gmb-axis In Cns Injuriesmentioning
confidence: 94%
“…The eubiotic gut is closely linked with good human health, and an imbalance of the GM either because of HHcy-led dysfunction of the 1-carbon metabolism or any other reason is associated with various system disorders (Figs. 1 and 2 ) [ 150 , 153 – 156 , 192 – 194 ]. Because of the importance of bi-directional relationship between the GM and TBI-associated pathophysiology, management of gut dysbiosis could serve as paradigm for a likely therapeutic target (Figs.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbial dysbiosis can potentially induce HS by influencing skin microbes through mediating systemic inflammatory pathways. 2 , 215 According to an interesting hypothesis, colonic dysbiosis resulting from high-fat diet results in inflammatory cytokine (e.g., TNF-α, IL-1β, and IL-17) elevation, and ultimately in formation of HS lesion by enhancing matrix metalloproteinase levels. 215 Probiotics are considered an effective option in treating HS for restoring a healthy cutaneous microbiome, as they are capable of replenishing the abundance of Cutibacterium spp., Corynebacterium , and Staphylococcus within the communities.…”
Section: Methodsmentioning
confidence: 99%
“…It has been hypothesised that enteric dysbiosis (potentially caused by a high-fat diet) elevates inflammatory cytokines such as Il-1β, Il-17, and TNF-α. This ultimately leads to an increased level of matrix metalloproteinases and subsequently HS lesion formation in susceptible individuals [105].…”
Section: Beyond the Skin Microbiomementioning
confidence: 99%